2014
DOI: 10.14453/aabfj.v8i4.5
|View full text |Cite
|
Sign up to set email alerts
|

The What, Why and How of Generic Skills: A Financial Planning Case Study

Abstract: Financial planning in Australia is moving away from its traditional characterisation as an "industry" and towards a "profession". A key feature of any profession is an educational framework that facilitates the development of technical knowledge and generic skills by students so that they can successfully transition into the workplace. The Australian Securities and Investments Commission (ASIC) is currently reviewing changes to that educational framework (ASIC 2011; ASIC 2013), while the Financial Planning Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The literature has presented that the acquisition and development of skills to be a financial planner is genderneutral. To acquire these skills, a prospective financial planner would require a learning strategy that draws on formal education combined with work-related learning and experience (Cameron et al, 2014). However, we contend that these skills are associated with being either masculine or feminine, and this association can inhibit women from obtaining or demonstrating these skills.…”
Section: The Values In An Evolving Financial Planning Professionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has presented that the acquisition and development of skills to be a financial planner is genderneutral. To acquire these skills, a prospective financial planner would require a learning strategy that draws on formal education combined with work-related learning and experience (Cameron et al, 2014). However, we contend that these skills are associated with being either masculine or feminine, and this association can inhibit women from obtaining or demonstrating these skills.…”
Section: The Values In An Evolving Financial Planning Professionmentioning
confidence: 99%
“…Cull and Sloan (2016) found that prioritizing a client's interest is a vital aspect of trust in financial planning. Other research highlights the gaps between the skills required by financial planning graduates and industry requirements (Cameron et al, 2014;Jackling & Sullivan, 2007;West et al, 2019). These gaps are in client-centered financial planning skills, where graduates must develop interpersonal skills, listening skills, communication skills, and questioning skills.…”
Section: The Values In An Evolving Financial Planning Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also can be used as skills and attribute in daily life as well as work-life since it covers basic competence and core competence including cognitive, personal, and interpersonal skills related to the carrier. Generic skill is highly needed to pursue higher education and a successful carrier ( (Cameron et al, 2014), generic science is a skill to support every discipline of studies and is potentially transferred to every context of higher education and the workplace. Not only transferring generic skills but also is important to enable students to apply their knowledge or disciplinary in every context (Jackson, 2013).…”
Section: Generic Science Skillsmentioning
confidence: 99%
“…By referring to recent high profile collapses, the authors suggest factors that can be considered by individuals when assessing the quality of any advice or service offered. In this theme of change and Professionalisation, Cameron, Brimble, Knutsen and Freudenberg (2014) examine the generic skills needed by financial planners; and which are currently seen to be most deficient. These authors recommendations aim to assist the financial planning industry moving further towards professional status and conduct.…”
Section: Editorial: Aabfj Volume 8 Issue 4 Special Issue In Financiamentioning
confidence: 99%